Integrasi Kearifan Lokal melalui Strategi Komuniasi Pengembangan Pariwisata di Perbatasan RI-PNG - Samdar Rery; Muhammad Nur Jaya; Indah Sulistiani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The tourism industry is one of the sources of regional foreign exchange that is enough to increase the region's original income, the RI-PNG border area in Jayapura City has many tourism locations, but tourism development is not a serious concern for the tourism office and the management of tourist attractions. Tourism development is still minimal and has not been integrated with local wisdom that can improve the community's economy. The purpose of this study is to describe the development of tourism through the integration of local wisdom with a communication approach in improving the community's economy, analyzing the process of integrating local wisdom in tourism development through local wisdom products. This research method uses a qualitative approach with Miles and Huberman model data analysis techniques, namely data collection, reduction, display, and conclusion drawing/verifying. The results of this study show that (1) communication of local wisdom development has not been done well in tourism development, especially participatory communication in increasing the empowerment of local communities through local wisdom products. (2) The use of communication media to encourage the progress of tourism has not been maximally carried out in promoting local wisdom resources.